Application of a stable Ag/TiO2 film in the simultaneous photodegradation of hormones - Lima, Karla VL; Emídio, Elissandro S [UNESP]; Pupo Nogueira, Raquel F [UNESP]; Vasconcelos, Nazaré do Socorro LS; Araújo, Adriana B (Wiley, 2020)
BACKGROUND: The natural hormones estrone (E1) and 17β-estradiol (E2) and the synthetic hormone 17α-ethynylestradiol (EE2) are excreted daily by humans and may reach water and wastewater treatment plants, which do not efficiently remove these estrogens. The aim of the present study was to evaluate the efficiency and reusability of Ag/TiO2 films as catalysts for simultaneous degradation of the hormones E1, E2 and EE2 in aqueous medium by heterogeneous photocatalysis and the contribution of reactive oxygenated species. The influence of aeration on the system and the effects of estrogen concentration and Ag/TiO2 film area were also evaluated in the photodegradation process. RESULTS: The photocatalytic degradation assays showed efficiency higher than 97% for E2 and EE2 (10 μg L−1) after approximately 3.5 h and above 95% for E1 (100 μg L−1) after 4.5 h. It was observed that hydroxyl radical is the main reactive oxidant species in the photodegradation process, responsible for 87, 86 and 79% degradation of E1, E2 and EE2 respectively. CONCLUSION: The treatment process applied using the Ag/TiO2 films proved to be very stable and efficient for the simultaneous degradation of the studied hormones up to 305 h of reaction period, obtaining a percentage of degradation above 90%. © 2019 Society of Chemical Industry.
Keywords: Ag/TiO2 films; endocrine disruptors; estradiol; estrone; heterogeneous photocatalysis